Clave taxonómica de ciliados epibiontes de Decapoda (Natantia) - Camacho G., Lucía (1989)
Identification keys are provided for the families and genera of epizoic ciliates present in Decapoda, Natantia. They include 10 families and 13 genera. The descriptions are based on previous reports and on the groups found in pond reared adult prawns of Macrobrachium rosenbergii.